2009
DOI: 10.1271/bbb.90371
|View full text |Cite
|
Sign up to set email alerts
|

TheCorynebacterium glutamicumNCgl2281 Gene Encoding an RNase E/G Family Endoribonuclease Can Complement theEscherichia coli rng::catMutation but Not therne-1Mutation

Abstract: The Corynebacterium glutamicum NCgl2281 gene encodes an RNase E/G family endoribonuclease having an additional N-terminal domain of unknown function. In this study, we constructed plasmids expressing the full length (FL) and the N-terminally truncated form (ÁN) of NCgl2281 and examined their complementation ability as to Escherichia coli rng::cat and rne-1 mutations. Both FL-and ÁN-NCgl2281 rescued the defects caused by the rng::cat mutation, i.e., accumulation of 16S rRNA precursor, overproduction of the AdhE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…1, a ⌬rneG mutant strain, D2281, grown on sodium acetate as the sole carbon source synthesized a large amount of protein with a molecular mass of ϳ45 kDa, compared with the wild type; the ⌬rneG mutant produced 2.3-fold Ϯ 0.4-fold (n ϭ 3) more 45-kDa protein than the wild type. The overproduction of the 45-kDa protein reverted to wildtype levels when the plasmid pCrneFL, carrying the rneG gene (36), was introduced into the D2281 strain (data not shown). The 45-kDa protein band was identified as ICL with a molecular mass of 47.3 kDa by mass spectrometry.…”
Section: Resultsmentioning
confidence: 94%
“…1, a ⌬rneG mutant strain, D2281, grown on sodium acetate as the sole carbon source synthesized a large amount of protein with a molecular mass of ϳ45 kDa, compared with the wild type; the ⌬rneG mutant produced 2.3-fold Ϯ 0.4-fold (n ϭ 3) more 45-kDa protein than the wild type. The overproduction of the 45-kDa protein reverted to wildtype levels when the plasmid pCrneFL, carrying the rneG gene (36), was introduced into the D2281 strain (data not shown). The 45-kDa protein band was identified as ICL with a molecular mass of 47.3 kDa by mass spectrometry.…”
Section: Resultsmentioning
confidence: 94%
“…This association is novel and suggests involvement in regulatory networks distinct from the type I and II enzymes. Corynebacterium glutamicum NCgl2281 encodes an RNase E that has been shown to be involved in the processing of 5S rRNA and in the regulation of the glyoxylate cycle (Maeda et al, 2009;Maeda and Wachi, 2012b). Intriguingly, expression of Cg-RNase E has been reported to complement an RNase G deficient strain of E. coli but not an RNase E deficient strain (Maeda et al, 2009).…”
Section: Type III Enzymesmentioning
confidence: 99%
“…C. glutamicum has one RNase E/G homolog (NCgl2281) and one RNase J homolog (NCgl1895) but no RNase Y homolog. The central region of NCgl2281 shows 39.1% similarity to E. coli RNase G and 37.8% similarity to the N-terminal catalytic region of E. coli RNase E. A previous study suggested that C. glutamicum RNase E/G was more related to E. coli RNase G than to RNase E (Maeda et al 2009). In this study, we show that although the NCgl2281 protein is not essential for cell viability, it is involved in the processing of 5S rRNA in C. glutamicum.…”
Section: Introductionmentioning
confidence: 90%
“…The pECt is an E. coli-C. glutamicum shuttle vector of moderate copy number (about 10 copies in C. glutamicum cells). The pCrneFL is a pECt-based NCgl2281 expression plasmid (Maeda et al 2009). Briefly, the cells were grown in L broth at 30°C.…”
Section: Construction Of Ncgl2281 Knockout Strainmentioning
confidence: 99%
See 1 more Smart Citation